Social networks as a journalistic communication tool: Volodímir Zelenski’s Digital Communication Strategy during the Ukraine war - Olivares García, Francisco J.; Román San Miguel, Aranzazu; Méndez Majuelos, Inés (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This paper analyzes the social media strategy of the President of Ukraine, Volodymyr Zelensky, during the first 30 days of the Russian invasion, between February 24 and March 25, 2022. The use of social media became a more effective communication tool than traditional channels, so his social media accounts served to keep the country informed of the actions the government was taking. At the same time, millions of people around the world were able to see the evolution of the war, according to Zelensky's point of view.